On P_3-degree Based Topological Indices of Fenofibrate Graph - V. Thukarama; H. M. Latharani; D. Soner Nandappa (International Journal of Mathematics And its Applications, 2025)
Topological indices are numerical descriptors of molecular structures, extensively used in chem-informatics, drug design, and material science to study molecular properties and predict biological activities. Fenofibrate, a clinically important lipid-lowering drug, is a molicule of significant interest in quantitative structure-activity relationship (QSAR) studies. This study focuses on computing degree-based topological indices of fenofibrate molecular graph. These indices, derived from the degree of vertices in the molecular structure, include: Zagreb Indices,Randic Index, Atom-bond connectivity, Geometric-Arithmetic Index,Harmonic Index. These are some Topological indices based on P_3-degrees.